The Importance of National Poverty Eradication Programme (NAPEP) on Income Improvement and Women Empowerment: Evidence from Kwara State, Nigeria - Abdussalam, O.Isiaka; Mohammad Haji Alias; Fuadah Johari (Universiti Sains Islam Malaysia, 2024)
Greater concern has been given to women as they are being considered as victim or prey of poverty by the international community as well as in Nigeria. This is partly because of what they are earning as income and its inequality around the world. However, the purpose of the paper is to examine the effects of the monthly income on the level of poverty alleviation of women under the National Poverty Eradication Programme (NAPEP) in Kwara State,Nigeria. The paper employs mixed methods as the questionnaire was designed and supplemented by the personal interview. Two hundred (200) respondents were chosen as sample size though stratified sampling technique. The data collected were analysed using descriptive and inferential statistics such as frequencies, percentages, and Paired sample t-test. Findings of the study reveal positive and significant effects of the monthly income on the poverty reduction and living condition of the respondents, as there was improvement in their income after their participation in the anti- poverty programme in the State. There should be meaningful financial support to augment the income of the poor. The paper strongly recommends the government to incorporate more poor women in the rural areas in its anti-poverty programme and also curb the rate of corruption in the State.